QUALITY OF COMMUNITY PARTICIPATION IN ELECTIONS - La ode Arwan; Andi; La ode Muhammad Arham; Wa ode Suharni; Fitri; Junaid Gazalin (Media Inovasi Pendidikan dan Publikasi, 2024)
Elections are a means of realizing people's sovereignty and are also the fairest competition arena for political parties. The community has a significant contribution by voting according to their aspirations in the general election process where the community as voters determines the winner. This research uses a qualitative approach and a literature study method approach. The results of this discussion show that participation in the community is very influential on the implementation of elections and is able to raise public awareness to participate in the political process, such as using their voting rights, monitoring elections, and providing motivation for the community to work directly as a successful team in supporting potential partners who have a vision. and a mission that is in line with his views. Community participation is very important in the implementation of general elections in the process of selecting executive and legislative members, because the community has quite a large role in the general election process where the community as voters determines victory in the general election process